1994
DOI: 10.1002/nur.4770170205
|View full text |Cite
|
Sign up to set email alerts
|

Arousal and stress response across the menstrual cycle in women with three perimenstrual symptom patterns

Abstract: The purpose of this study was to compare arousal levels and stress response across menstrual cycle phases in women with three perimenstrual symptom patterns. Women with low symptom severity (LS, N = 28), were compared with those with a premenstrual syndrome (PMS, N = 15) and premenstrual magnification (PMM, N = 19) pattern across postmenses and premenses phases. Each woman was assessed during relaxation and in response to mental task and symptom imaging stressors during a postmenses and premenses day. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Symptoms need to be rated daily over at least two months to confirm the diagnosis (American Psychiatric Association, 1994). Some studies show higher heart rate, greater skin conductance, or greater norepinephrine levels throughout the menstrual cycle (Palmero and Choliz, 1991; Asso and Magos, 1992; Girdler et al, 1998) or just in the late-luteal phase in women with severe PMS (Woods et al, 1994) and others show no differences in these measures compared to controls (Van den Akker and Steptoe, 1987, 1989; Girdler et al, 1993). Studies of HRV in PMS have also produced inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms need to be rated daily over at least two months to confirm the diagnosis (American Psychiatric Association, 1994). Some studies show higher heart rate, greater skin conductance, or greater norepinephrine levels throughout the menstrual cycle (Palmero and Choliz, 1991; Asso and Magos, 1992; Girdler et al, 1998) or just in the late-luteal phase in women with severe PMS (Woods et al, 1994) and others show no differences in these measures compared to controls (Van den Akker and Steptoe, 1987, 1989; Girdler et al, 1993). Studies of HRV in PMS have also produced inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…One study (4) reported that women with PMS have a higher resting heart rate than controls in the late-luteal phase, consistent with altered autonomic nervous system function, but others have failed to replicate this effect (5,6). Measures of skin conductance, used as an index of sympathetic tone, have also produced conflicting results, with some studies reporting greater skin conductance in women with PMS (7), others reporting no difference between women with PMS and controls (8), and yet others reporting higher levels of skin conductance pre-menses than post-menses in women with PMS, an effect opposite to that seen in controls (9).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Epperson et al (2007) found an effect of cycle phase with greater acoustic startle responses during luteal phase testing (defined as days –1 to –7 menses onset) compared to follicular phase testing in women with PMDD. Similarly, Woods et al (1994) found a significant effect of cycle phase and PMS symptom severity with women meeting criteria for PMS demonstrating greater electromyogram and skin conductance responses to laboratory stressors during the luteal phase of the menstrual cycle (defined as days –1 to –7 menses onset) compared to less symptomatic women. For additional discussion of these and other incongruities see Moline et al (2003).…”
Section: Introductionmentioning
confidence: 85%
“…Briefly, the American College of Obstetricians and Gynecologists’ guidelines for diagnosis of PMS (ACOG, 2000) and the American Psychiatric Association’s guidelines for diagnosis of PMDD (APA, 2000) require symptom assessment during the 5 to 7 days prior to menses to capture symptom peaks which may occur at that time (Stoddard et al, 2007) and remit with menses onset or the start of the follicular phase (APA, 2000). Research from our labs have shown that the premenses week (days 1 to 7 prior to menses onset) was a robust estimate of the time frame during which ovarian steroids influenced stress reactivity (Woods et al, 1994) and days 7–10 post-ovulation yielded psychophysiological stress reactivity patterns distinct from the follicular phase (Lustyk et al, 2010). As the 7–10 day post-ovulation luteal window also captures the symptom peak period (Stoddard et al, 2007) that same luteal window was used in the present study.…”
Section: Methodsmentioning
confidence: 99%